2001
DOI: 10.1046/j.1523-1755.2001.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin in transplantation: A review of the evidence

Abstract: Rapamycin in transplantation: A review of the evidence. The calcineurin inhibitors have been the mainstays of immunosuppression for solid organ transplantation over the last two decades, but nephrotoxicity limits their therapeutic benefit. Rapamycin is a new drug with both immunosuppressant and antiproliferative properties that has a unique mechanism of action distinct from that of the calcineurin inhibitors. It has a role as a maintenance immunosuppressant either alone or in combination with a calcineurin inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
299
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(314 citation statements)
references
References 102 publications
11
299
0
4
Order By: Relevance
“…Rapamycin is regarded as a global inhibitor of cell cycle progression, although patients do not experience a higher incidence of infections that would suggest a global state of immunosuppression (clinical trials reviewed in Ref. 4). We anti-bcl-x L antibody, and proteins were visualized by ECL (lower panel).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapamycin is regarded as a global inhibitor of cell cycle progression, although patients do not experience a higher incidence of infections that would suggest a global state of immunosuppression (clinical trials reviewed in Ref. 4). We anti-bcl-x L antibody, and proteins were visualized by ECL (lower panel).…”
Section: Discussionmentioning
confidence: 99%
“…The potent immunosuppressive activity of rapamycin has led to its wide clinical use in solid organ transplantation (reviewed in Ref. 4). More recent studies demonstrated successful islet cell transplantation in patients with type I diabetes treated with low dose rapamycin in combination with humanized anti-IL-2 1 receptor monoclonal antibody (mAb) and FK506, which prevented autoimmune destruction of islet cells (5).…”
mentioning
confidence: 99%
“…[126][127][128][129] Several rapamycin analogs have already been approved for use in transplant patients as immunosuppressants. 130 RAD001 and CCI-779 are currently in phase I and II trials, respectively, as anticancer agents. 125 The PI3-K-Akt pathway appears to be a promising therapeutic target for cancer treatment.…”
Section: Molecular Biomarkers Based On Akt Activitiesmentioning
confidence: 99%
“…MTIs are a class of signal transduction inhibitors with anticancer activity that were initially developed as immunosuppressive agents. [2][3][4][5] Rapamycin, a macrocyclic lactone produced by Streptomyces hydroscopicus, 6 was the first MTI to be used in a clinical setting. Rapamycin is well tolerated in humans.…”
mentioning
confidence: 99%